Book Review: Jack D. Eller, From Culture, to Ethnicity, to Conflict: An Anthropological Perspective on International Ethnic Conflicts - Patty Zakaria (Romanian Journal of European Affairs, 2011)
From Culture, to Ethnicity, to Conflict: An Anthropological Perspective on International Ethnic Conflicts, Eller illustrates that the characteristics used to define ethnicity cannot be freely applied to all groups since group perception of what their ethnicity encompasses vary significantly. Further, Eller points out that once a group becomes self-conscious of their difference within society, this realization leads to the initiation of group mobilization, from this viewpoint a group is then considered a nationalistic group as opposed to a mere ethnic group within society. This was evident in Sir Lanka when both the Sinhalese and the Tamils were aware of their differences and had established their own nationalistic group, wherein each nationalistic group seeks to control the island. Taken as a whole, Eller’s From Culture, to Ethnicity, to Conflict: An Anthropological Perspective on International Ethnic Conflicts, offers an insightful and extensive understanding of ethnicity and conflict, by arguing that ethnicity and conflict have developed out of modern social condition and circumstances, as opposed to primordial dynamics. The move away from primordial understanding sheds light into why once dormant groups become politically active as in the cases presented by Eller.